EFFECT OLIVE OIL CREAM ON AMOUNT OF COLLAGEN ON HEALING PROCESS OF INCISION WOUND LIPS (LABORATORY RESEARCH) - Susanto, Dinda Maretha Myke; Rochmah, Yayun Siti; Poetri, Adisty Restu; Rahman, Erwid Fatchur (Jurnal Medali, 2025)
Background: An incision wound is a type of open wound obtained using a scalpel by paying attention to the size, location and purpose of the wound. Collagen has an important role during the wound healing process. The content that can trigger the formation of collagen is phenolic compounds such as oleuropein, oleocanthal, and luteolin that can be found in olive oil. This study aims to determine the effect of olive oil cream 5% on the amounts of collagen on incision wounds process.Method: A quasy experimental design in vivo with a post-test only control group design on 12 wistar rats. The control group and the experimental group with 5% olive oil cream. Incision wounds was seen from the amount of collagen using One-Way Anova analysis.Result: The study showed that there was a significant effect of 5% olive oil on the amount of collagen with a significance of 0.000 (0<0.05).The results between the control group and the treatment had significant differences on 3th and 5th days.Conclusion: The conclusion is that there is an effect of giving 5% olive oil cream on the amount of collagen in the healing process of wistar incision lips.